(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Vaccination indisputably remains one of the most critical interventions in modern public health, serving as the primary mechanism for establishing herd immunity and halting the transmission of severe infectious diseases. However, the biological efficacy of vaccines is frequently undermined by complex socio-behavioral factors, including digital misinformation, political polarization, and fragmented public health infrastructure.